Effectiveness of Featured Product of Rural Areas Program (Prukades) in Improving The Economy of Teluk Village Community Pandeglang Regency - Rida Aulia; Sukendar; Ahmad Sururi (ADI Publisher, 2020)
The purpose of this study was to analyze on how the effectiveness of the Featured Product ofRural Areas Program (Prukades) in improving the economy of rural communities and to determineon how the level of success of Featured Product of Rural Areas Program (Prukades) in improvingthe economy of the community. This study used descriptive study with analytical descriptiveapproach. The technique of collecting data was conducted by using interviews, observation andquestionnaire. Respondents in this study were 23 respondents who are actively involved inPrukades with data analysis techniques that were used to measure the effectiveness of Prukadesby using simple statistical methods and the submission of questions presented in the form of aquestionnaire, then of the response is given a score. These results indicated that the program ofPrukades in Teluk Village of Pandeglang Regency, included into the category of quite effective.Referring to the four indicators of the effectiveness used, that are the appropriate targeting,socialization, objectives and monitoring, the indicator of monitoring conducted by the part ofDPMPD remains a constraint for the community, because even though it is regularly checked,people still do not feel the impact. And the success level of Prukades program is indicated by theabsorption of 20 members who joined from three types of Prukades in Teluk Village.